STUDI FENOMENOLOGI PARTISIPASI POITIK DIGITAL MAHASISWA SURABAYA DI TWITTER (The Commercium, 2021)
Political participation is now increasingly happening on digital platforms, where people present various information that can lead to participation, which is one of the important aspects of democracy. This study discusses the digital political participation of Surabaya students on Twitter. The method used in this research data analysis is the phenomenological method. This study uses a descriptive qualitative approach. The data source of this research is in-depth interviews with eight Surabaya students from various groups, with informants who have been selected according to the criteria, namely: share information (retweet), make tweets, and only read (like). And to find out how the informants behave in responding to politics. The purpose of this study was to determine the political behavior of Surabaya students on Twitter. The results of this study show that there are still many young people participating who do not dare to express their political stance because of their passive participation in politics for various reasons that make them more afraid to express their opinions. Even so, the informants understand and are aware of the problems that occur in the government and choose to be passive when there is a conflict. But there are still those who care and do not feel threatened when they express their political stance on social media. Future research is expected to find other ways to analyze political participation. The researcher also hopes that this research can be used as a reference for further research related to attitudes, participation, and also political communication.